2018
DOI: 10.1093/humrep/dey072
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs in seminal plasma are markers of the origin of azoospermia and can predict the presence of sperm in testicular tissue

Abstract: STUDY QUESTIONAre exosomal microRNAs (miRNAs) in seminal plasma (SP) useful as markers of the origin of azoospermia and the presence of sperm in the testis?SUMMARY ANSWEROur study demonstrated the potential of several miRNAs contained in small extracellular vesicles (sEVs) of seminal fluid as sensitive and specific biomarkers for selecting those azoospermic individuals with real chances of obtaining spermatozoa from the testicular biopsy.WHAT IS KNOWN ALREADYThere are no precise non-invasive diagnostic methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
153
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(164 citation statements)
references
References 37 publications
(53 reference statements)
8
153
0
3
Order By: Relevance
“…However, among the studies reported to date there is a wide variety of findings and so far neither one single microRNA nor any particular panel of microRNAs has evolved to be applicable for routine clinical diagnostics (Wu et al , ; Hu et al , ; Corral‐Vazquez et al , ; Barceló et al , ; Harchegani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, among the studies reported to date there is a wide variety of findings and so far neither one single microRNA nor any particular panel of microRNAs has evolved to be applicable for routine clinical diagnostics (Wu et al , ; Hu et al , ; Corral‐Vazquez et al , ; Barceló et al , ; Harchegani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the stability of seminal plasma miRNAs as a biomarker has been widely discussed (Barcelo, Mata, Bassas, & Larriba, ; Wang et al, ; Wu et al, ; Zhi et al, ). Wang et al evaluated the stability of miRNAs (miR‐9, miR‐106b and miR‐202) expression by repeated freezing and thawing of seminal plasma and incubation at room temperature and 4°C for different durations.…”
Section: Discussionmentioning
confidence: 99%
“…Zhi et al found that the expression level of seminal plasma miR‐192a in patients who successfully ejaculated after varicocele repair was significantly higher than that in patients who failed. In another recent study, Barcelo et al () used differential high‐throughput miRNA profiling techniques for miRNA quantitative PCR plates to analyse differences in seminal plasma exosomes in azoospermia and fertile individuals. Their findings have revealed altered miRNAs in seminal plasma exosomes that may be involved in the process of azoospermia origin and testicular spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the miRNAs detected in seminal plasma, five miRNAs (miR‐629‐3p, miR‐200b‐3p, miR‐425‐3p, miR‐33b‐3p and miR‐141‐3p) were previously described as being among the most stably expressed miRNAs in seminal plasma‐derived exosomes (Barcelo, Mata, Bassas, & Larriba, ). MiR‐141‐3p was reported to be stable in seminal plasma (Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%